ANALYSIS OF APBDeS MANAGEMENT IN IMPROVING THE ACCOUNTABILITY OF THE VILLAGE GOVERNMENT IN SEKARAN DISTRICT, LAMONGAN REGENCY - kusuma Wijaya (Universitas Teuku Umar, 2022)
The village is a social agency that has a very important position in the community. Based on Law Number 6 of 2014, it requires villages to be more independent in managing the government and various resources owned, including financial management and village-owned wealth. This study aims to find out how far the village government accountability principle is applied in the management of the Village Revenue and Expenditure Budget (APBDes) in Sekaran District Village, Lamongan Regency in 20 19-2021 through activities that include: Planning, Implementation, Reporting, and Accountability.The method used in this study is descriptive qualitative. This research was conducted in Sekaran District Village, Lamongan Regency. The object in this study is the Village Revenue and Expenditure Budget (APBDes) in Sekaran District, Lamongan Regency. Sekaran Subdistrict has 21 villages. The samples in this study took 8 (eight) villages in Sekaran District, Lamongan Regency. The villages include Bugel Village, Bulutengger Village, Karang Village, Kembangan Village, Latek Village, Siman Village, Trosono Village, and Kebalankulon Village.The results of this study show that the Village Government in Sekaran Subdistrict Village, Lamongan Regency has applied the principle of accountability in the management of the 2012019-2021 fiscal year APBDes. In general, the principle of accountability in Sekaran Subdistrict, Lamongan Regency, has been running well, although there are still weaknesses that still have to be corrected.Desa merupakan instansi sosial yang mempunyai posisi sangat penting di masyarakat. Berdasarkan UU Nomor 6 Tahun 2014, menuntut desa untuk lebih mandiri dalam mengelola pemerintahan dan berbagai sumber daya yang dimiliki, termasuk pengelolaan keuangan dan kekayaan milik desa. Penelitian ini bertujuan untuk mengetahui seberapa jauh penerapan prinsip akuntabilitas Pemerintah Desa dalam pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) di Desa Kecamatan Sekaran Kabupaten Lamongan tahun 2019-2021 melalui kegiatan yang meliputi: Perencanaan, Pelaksanaan, Pelaporan, dan Pertanggungjawaban.Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Penelitian ini dilakukan di Desa Kecamatan Sekaran Kabupaten Lamongan. Objek dalam penelitian ini adalah Anggaran Pendapatan dan Belanja Desa (APBDes) yang ada di Desa Kecamatan Sekaran Kabupaten Lamongan. Kecamatan Sekaran memiliki 21 desa. Sampel dalam penelitian ini mengambil 8 (delapan) desa di Kecamatan Sekaran Kabupaten Lamongan. Desa tersebut meliputi Desa Bugel, Desa Bulutengger, Desa Karang, Desa Kembangan, Desa Latek, Desa Siman, Desa Trosono, dan Desa Kebalankulon.Hasil penelitian ini menunjukkan bahwa Pemerintah Desa di Desa Kecamatan Sekaran Kabupaten Lamongan telah menerapkan prinsip akuntabilitas dalam pengelolaan APBDes tahun anggaran 2019-2021. Secara umum prinsip akuntabilitas di Desa Kecamatan Sekaran Kabupaten Lamongan sudah berjalan dengan baik, meskipun masih ada kelemahan yang masih harus diperbaiki.